Manifest Social Justice Judging from the Principles of Islamic Law on Corporate Criminal Aspects of the Environment: Literature Review - Rimsyahtono; Sambas, Nandang; Januarita, Ratna; Imaniyati, Neni Sri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Corporate punishment in the environmental aspect has not led to social justice based on Islamic law principles because of the lack of attention to the community as victims who suffer losses due to environmental pollution, which should be a life support. This study aimed to realize that social justice based on Islamic law principles incorporates punishment in environmental aspects for the future. This type of research uses a normative legal typology to approach the principles, systematics, and level of legal synchronization of legislation based on Islamic Law and Law No. 32 of 2009 concerning Environmental Protection and Management. Secondary data obtained through library studies were analyzed descriptively. The results show that the nature of corporate punishment in environmental aspects in Islamic Law aims to prevent corporations from repeating their actions, prevent other corporations from participating in environmental pollution, and foster corporations that have polluted the environment. Furthermore, the embodiment of social justice based on Islamic law principles incorporate punishment in the environmental aspect must contain the values of corporate culture and community development. Social justice is in line with the principle of the benefit of the people in Islamic Law, where each punishment contains aspects of paying attention to victims of crime.